Mathematical modeling of failure process of AlMg2.5 alloy during highand very high cycle fatigue - Bilalov, Dmitriy Al’fredovich; Bayandin, Yuriy Vital’yevich; Naimark, Oleg Borisovich (Computational Continuum Mechanics, 2018)
Forecasting the limit of endurance in the high- and very high cycle loading range (102-1010) is an actual problem of aircraft engine construction and high-speed rail transport. It involves the development of models and their experimental verification, taking into account the stages of development of damage and the development of fatigue cracks in a damaged medium. The proposed model of the damage evolution, taking into account the kinetics of defects and effects of microplasticity, was used to study the process of fatigue failure of a structural alloy AlMg2.5. The model parameters were identified and verified using experimental data on static, dynamic and fatigue loading, as well as tests at various temperatures. The Weller curve is numerically constructed. It agrees well with experiment in the range of high cycle fatigue. The duality effect of the S-N diagram is described. A computational experiment on the effect of dynamic loading on fatigue strength showed a weak dependence of the fatigue limit on preliminary dynamic strain. It is confirmed by experimental data. Comparison of various mathematical packages and numerical methods for solving the constructed system of differential equations carried out. The optimality of the Adams method and its modifications for numerical integration of the problem under consideration is shown. Wolfram Mathematica is the preferred software package for numerical solution. The problem of convergence of the numerical solution has been investigated.
Keywords: numerical simulation; very high cycle fatigue; duality of the Weller curve; cyclic loading; fatigue failure; endurance limit